Muscle morphology of the lower leg in ambulant children with spastic cerebral palsy - Pitcher, C.; Elliott, Catherine; Valentine, J.; Stannage, K.; Williams, Sian; Shipman, P.; Reid, S. (John Wiley & Sons, Inc., 2018)
Introduction: In this study we aimed to determine the lower limb morphological characteristics of skeletal muscle of ambulant children with spastic cerebral palsy (CP) and typically developing (TD) children. Methods: Seventeen children with spastic diplegic CP (10 boys and 7 girls, 5–12 years of age, Gross Motor Function Classification System [GMFCS] level I or II) and 19 TD children (8 boys and 11 girls, 5–11 years of age) underwent lower limb T1-weighted MRI. Morphological characteristics of the triceps surae, including muscle volume, anatomical cross-sectional area, muscle length, and subcutaneous adipose tissue, were digitally quantified, and the proportional distribution calculated. Results: Children with GMFCS II had significantly reduced muscle volume, cross-sectional area, and muscle length, and increased subcutaneous fat compared with TD children. Children classified as GMFCS II consistently exhibited the greatest deficits in all morphology variables. Discussion: Morphological variables were significantly different between the groups. These alterations have the potential to influence the functional capabilities of the triceps surae muscle group. Muscle Nerve, 2018.